Association between the hemoglobin A1c/High-density lipoprotein cholesterol ratio and stroke incidence: a prospective nationwide cohort study in China - Chaojuan Huang; Hongtao You; Yuyang Zhang; Ligang Fan; Xingliang Feng; Naiyuan Shao (Lipids in Health and Disease)
Abstract Background Stroke has emerged as an escalating public health challenge among middle-aged and older individuals in China, closely linked to glycolipid metabolic abnormalities. The Hemoglobin A1c/High-Density Lipoprotein Cholesterol (HbA1c/HDL-C) ratio, an integrated marker of glycolipid homeostasis, may serve as a novel predictor of stroke risk. Methods Our investigation utilized data from the China Health and Retirement Longitudinal Study cohort (2011–2018). Stroke cases were identified based on self-reported, physician-confirmed diagnoses. Logistic regression models were established to determine the correlation between HbA1c/HDL-C and stroke prevalence (2011) as well as between cumulative mean HbA1c/HDL-C (2011–2015) and new stroke incidence (2015–2018). Additionally, smoothed curve fitting, subgroup analyses, and interaction tests were conducted to ensure the robustness of the findings. Results In the cross-sectional analysis, 8,502 participants were enrolled, of whom 189 had a history of stroke. Our findings revealed a significant positive linear relationship between HbA1c/HDL-C and stroke prevalence after adjusting for covariates (OR: 1.26, 95% CI: 1.09–1.45). When HbA1c/HDL-C was categorized into tertiles, only the highest tertile (T3) showed a significant correlation with stroke prevalence compared to the lowest tertile (T1) (OR:1.71, 95% CI: 1.05–2.77). In the longitudinal analysis of 5,165 participants, 336 cases of new-onset stroke were identified over a follow-up period of 7 years. Adjusting for confounders, individuals with higher cumulative mean HbA1c/HDL-C exhibited an increased likelihood of new stroke incidence (OR: 1.14, 95% CI: 1.01–1.29). Using the T1 of cumulative mean HbA1c/HDL-C as a reference, the fully adjusted OR for stroke was 1.65 (95% CI: 1.21–2.24) in T2 and 1.54 (95% CI: 1.08–2.19) in T3. The predictive value of the HbA1c/HDL-C in stroke risk assessment have been significantly improved compared to the traditional HDL-C and HbA1c. Consistent associations were observed across most stratified subgroups. Conclusions Elevated baseline and cumulative mean HbA1c/HDL-C levels are significantly associated with an increased risk of stroke among middle-aged and older individuals in China, underscoring the potential of HbA1c/HDL-C as a clinical marker for long-term stroke risk assessment and prevention strategies.